The Role of Self-Efficacy and Social Support for Grit in Master of Professional Psychology Students - Lucy Lutviantari, Chintya; Wulan Saptandari, Edilburga (KnE Social Sciences, 2024)
Grit is a trait or personality that must be possessed by individuals, especially students who are studying in the Master of Professional Psychology program. Students who have grit can demonstrate good academic performance and achieve planned long-term goals. This study aims to determine the role of self-efficacy and social support for grit in Master of Professional Psychology students in Indonesia. The participants of this study amounted to 210 students from various universities and specializations majoring in psychology who were collected using purposive sampling techniques. The research instruments used were self-efficacy scale, social support scale, and grit scale. Data were analyzed by multiple regression analysis using SPSS 24. The results of multiple regression tests show that there is a significant role between self-efficacy and social support for the grit of Master of Professional Psychology students (R square = 0.654, F = 195.278, p < 0.05). Keywords: self-efficacy, social support, grit, professional psychology master students